Tunneling and magnetic properties of triple quantum dots: Электронные свойства низкоразмерных систем - Kikoin, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Unconventional features of Kondo effect in quantum tunneling through triple quantum dots are reviewed. Special attention is paid to the interplay between continuous rotation symmetries in the spin space and discrete point symmetries in the real space. Specific properties of Kondo effect in linear, cross, fork and triangular configurations of triple quantum geometries dot are discussed.